Formulation and in vitro/in vivo Evaluation of Zidovudine Contained in Solidified Reverse Micellar Delivery System of Immune Compromised Rats - Uronnachi Emmanuel M,Ogbonna John DN,Kenechukwu Franklin C,Attama Anthony A,Okore Vincent C. (Journal of Applied Pharmaceutical Science, 2013)
Aim of the study was to study the in vitro and in vivo evaluation and correlation of zidovudine (AZT) loaded solidified reverse micellar microparticles (SRMMs). The SRMMs composed of goat fat and Phospholipon® 90H in various ratios (1:1, 2:1, 3:1 and 2:3) were prepared by melt dispersion method. AZT (1% w/w, 2% w/w, 3% w/w and 5% w/w) were incorporated into the SRMMs and preliminary analysis of the preparations on their stability were done visually. The 1:1 formulation was evaluated for the particle size, percentage yield and in vitro studies which was done using SGF and SIF. The in vivo study was done using Wistar albino rats and the in vitro-in vivo correlation (IVIVC) was determined by plotting a graph of the fraction of drug absorbed in vivo versus the fraction of drug released in vitro. The yield of the goat fat extraction was 58%. The particle size and yield of the solid lipid microparticle (SLM) containing 1% w/w of AZT were 5.10 ± 0.10µm and 86.3 ± 4.70% respectively. The fraction of drugs absorbed in vivo were 0.102 µg, 0.114 µg, 0.115 µg, 0.134 µg and 0.123 µg for 1h, 3 h, 5 h, 8 h and 12 h respectively. A 1:1 ratio of goat fat and Phospholipon® 90H with a high value of correlation coefficient (r2 = 0.909) suggested good level-A correlation between the in vitro-in vivo data of the SLM obtained in the study.
Keywords: Solidified reverse micellar microparticle (SRMM), li